(untitled) (Journal of Economic Research & Business Administration, 2016)
Instability of world economy, characteristic for the present, causes the dominating role of the preventive risk management allowing enterprise structures purposefully and with anticipation to react to the arising risks, preventing threat of inadmissible decrease in efficiency of business activity under the influence of risks. In article the main characteristics inherent in tax risk are defined functions of tax risk are allocated. Also need of the organization of scientific researches, uses of various methods of decrease in tax risks at the enterprise, development of strategy of management of risk, in the form of forecasting of risks locates. also measures for their account, for the purpose of decrease in tax risks are offered. Conclusions are drawn that tax risks in the Republic of Kazakhstan are subject to the analysis and an assessment, them it is possible and it is necessary to operate.